2004
DOI: 10.1111/j.1460-2695.2004.00712.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of solidification structure on tear resistance of Al–7% Si–0.4% Mg cast alloys

Abstract: A B S T R A C TThe tear resistance behaviour of Al-7% Si-0.4% Mg cast alloys was examined using Kahntype tear test specimens. Tests were performed for two permanent mould casts with an ordinary dendrite structure and a semi-liquid die cast with a globular cell and fine grain structure. The microstructure of the two permanent mould casts was controlled by the cooling rates and the addition of Ti elements. Tear resistance was evaluated by the 'popin' stress, the energies required for crack initiation, UE i and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Suárez-Peña and Asensio-Lozano [ 84 ] found that, at a higher Ti/Sr ratio (Ti:Sr = 1:1), the poisoning effect is more pronounced than at a lower Ti/Sr ratio (Ti:Sr = 3:5). However, Ibrahim et al [ 85 ] stated that combined addition of grain refiners along with Sr to the A356 alloy could result in reducing the grain size of α-Al dendrites as well as changing the morphology of the eutectic Si particles.…”
Section: Combined Effect Of Ti/b and Srmentioning
confidence: 99%
See 2 more Smart Citations
“…Suárez-Peña and Asensio-Lozano [ 84 ] found that, at a higher Ti/Sr ratio (Ti:Sr = 1:1), the poisoning effect is more pronounced than at a lower Ti/Sr ratio (Ti:Sr = 3:5). However, Ibrahim et al [ 85 ] stated that combined addition of grain refiners along with Sr to the A356 alloy could result in reducing the grain size of α-Al dendrites as well as changing the morphology of the eutectic Si particles.…”
Section: Combined Effect Of Ti/b and Srmentioning
confidence: 99%
“…Moreover, the reduction in the grain size improves the distribution of the porosity, which also attributes to an increase in the toughness [ 84 ]. It should be noted that the modification of the Al-Si eutectic has little effect on the toughness [ 85 , 86 ]. Obviously, fatigue properties are optimal when porosity and surface defects are minimal [ 10 ].…”
Section: Grain Size–mechanical Properties Relationshipmentioning
confidence: 99%
See 1 more Smart Citation